The scent of God : a memoir - Bissell, Beryl Singleton (New York : Counterpoint, 2006)
As a teenager, Beryl Bissell entered a cloistered monastery of the Poor Clares in New Jersey, following her passion and believing God had called her to this way of life. After fifteen years in the convent, enduring periods of bliss as well as inner torment and obsessive disorders, she is called to Puerto Rico to care for her ailing father. There she meets and falls in love with handsome Italian priest, Padre Vittorio. For the next three years, Beryl struggles to reconcile her spiritual longing with human desire while maintaining a chaste and loving relationship with Vittorio. Throughout the events that follow, the author tells a powerful story of love, death, guilt, and redemption--a pilgrimage that reaches beyond dogma to personal truth and evokes a transformation that changes not only Beryl, but the lives of those around her.
Includes bibliographical references (p. 291)
Keywords: Bissell, Beryl Singleton; Nuns -- United States -- Biography; Spirituality -- Biography; Catholic -- Biography